Translation strategies of menacing speech act in political discourse from English into Russian - Bulbul Matay, Shakhidam Khamrayeva, Aybarsha Islam, Agnur Khalel (Opción, 2019)
The aim of the article is to investigate translation strategies of menacing speech act in political discourse from English into Russian via qualitative comparative analysis of other scholars’ works in this field. As a result, in the translation of menacing speech acts in political discourse, we attempted to preserve the author’s intention to convey his aggressive attitude towards the opponent. The diversity of the content of the political discourse allows us to conclude that not only a menacing speech act should be studied, but also other topics of the English-language political discourse and any other.